2021
DOI: 10.1038/s12276-021-00584-0
|View full text |Cite
|
Sign up to set email alerts
|

Multiplexed targeting of miRNA-210 in stem cell-derived extracellular vesicles promotes selective regeneration in ischemic hearts

Abstract: Extracellular vesicles (EVs) are cell derivatives containing diverse cellular molecules, have various physiological properties and are also present in stem cells used for regenerative therapy. We selected a “multiplexed target” that demonstrates multiple effects on various cardiovascular cells, while functioning as a cargo of EVs. We screened various microRNAs (miRs) and identified miR-210 as a candidate target for survival and angiogenic function. We confirmed the cellular and biological functions of EV-210 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…Moreover, one study demonstrated that miR-210 can regulate the expression of EFNA3 to promote sensory axon regeneration in adult mice [ 48 ]. Importantly, several studies indicate that miRNA-210 from extracellular vesicles could regulate the expression of EFNA3 to promote angiogenesis in ischemic hearts [ 49 ], oral squamous cell carcinoma [ 34 ], acute myocardial infarction [ 49 ], and ischemic disease models [ 50 ]. These studies suggest that abnormal expression of miR-210 is a possible cause of high EFNA3 expression in LUAD.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, one study demonstrated that miR-210 can regulate the expression of EFNA3 to promote sensory axon regeneration in adult mice [ 48 ]. Importantly, several studies indicate that miRNA-210 from extracellular vesicles could regulate the expression of EFNA3 to promote angiogenesis in ischemic hearts [ 49 ], oral squamous cell carcinoma [ 34 ], acute myocardial infarction [ 49 ], and ischemic disease models [ 50 ]. These studies suggest that abnormal expression of miR-210 is a possible cause of high EFNA3 expression in LUAD.…”
Section: Discussionmentioning
confidence: 99%
“…Coronary artery diseases, a representative cardiovascular disease, are caused by atherosclerosis and are known to cause arrhythmias and myocardial infarction. In order to maintain the homeostasis of various cells (cardiac cells, fibroblasts, lymphocytes, mast cells, and macrophages) present in the cardiovascular system and the difficulties in cardiac regeneration and repair ( 14 ), so stem cell-derived EV therapy is essential, especially the special treatment of EV-derived miRNAs functioned as multiplexed targeting.…”
Section: Regenerative Medicine For Tissue Repairmentioning
confidence: 99%
“…Using a lentivirus, miRNA-EV system was constructed that can stably produce miRNA-210, which plays a pivotal role in cardiovascular cells, in adult stem cell EVs. It was shown that miRNA-210 in stem cell-derived EVs controlled cardiac cell death by targeting protein tyrosine phosphatase 1B (PTP1B) and death-associated protein kinase 1 (DAPK1), and also controlled angiogeneisis of vascular cells by targeting Ephrin A (EFNA3), with no effect on cardiac fibroblasts ( 14 ). Similarly, substances targeted by miRNA-133a expressed in adult CPC were discovered through bioinformatic prediction including BMF (Bcl-2 modifying factor) and BIM (Bcl2l11), which are potent proapoptotic factors, a serine threonine kinase STK4 (formerly Mst1) activated by oxidative stress, and Foxo1 that is a critical promotor of cardiomyocyte survival upon oxidative stress conditions.…”
Section: Regenerative Medicine For Tissue Repairmentioning
confidence: 99%
See 1 more Smart Citation
“…The ENCODE consortium shows that more than 80% of the human genome are transcribed into RNAs, whereas less than 2% of the human genome lastly encodes proteins [ 10 ]. Thus, the protein non-coding transcripts are significantly more diverse than protein-coding mRNAs [ 11 13 ]. Long non-coding RNAs (lncRNAs) are the most diverse class of non-coding transcripts, which also have diversely regulatory roles in various pathophysiological processes [ 14 19 ].…”
Section: Introductionmentioning
confidence: 99%